2015
DOI: 10.1007/s12665-015-4072-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic freeze–thaw as a mechanism for water and salt migration in soil

Abstract: Freeze-thaw action acts as a controlling mechanism for redistributing soil water and salt. The paper focuses on the factors that influence soil water and salt migration and uses experimental results to analyze the mechanism of cyclic freeze-thaw in which the temperature gradient is the principal factor for water and salt transfer. Salt redistribution in soil occurs as a result of the integrated effects of convection, diffusion, and numerous chemical and physicochemical processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 18 publications
(12 reference statements)
3
45
1
Order By: Relevance
“…Water migrates up and down to freezing fronts during soil freezing (Bing et al, 2015;Brown, 1967). This creates air pockets, even in inundated soils, as we saw in our soil cores in agreement with recent studies using CT scans of soil cores collected near Utqiaġvik (Raz-Yaseef et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water migrates up and down to freezing fronts during soil freezing (Bing et al, 2015;Brown, 1967). This creates air pockets, even in inundated soils, as we saw in our soil cores in agreement with recent studies using CT scans of soil cores collected near Utqiaġvik (Raz-Yaseef et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the processes leading to these high emissions during spring, soil freezing processes must be considered. During soil freeze, water migrates to top and bottom freezing fronts leaving air pockets in the active layer (Bing, He, & Zhang, 2015; Brown, 1967). Salts and ions are pushed out of freezing water fronts (Bing et al., 2015; Gray & Granger, 1985), which also occurs with gases.…”
Section: Introductionmentioning
confidence: 99%
“…Freezing and thawing can change soil structure, as well as physical and chemical properties, and affect the spatial and temporal changes of soil moisture, temperature, and salt [24,25]. Temperature is the driving force of soil water and salt migration under freezing and thawing conditions [26]. The freezing process results in a rapid decrease in temperature, and the soil water freezes, while the ablation process heats up rapidly to thaw and evaporate the frozen water.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of factors that influence the characteristics of frozen-thawed soil. Firstly, the type of soil-which includes moisture content [6][7][8][9] and pore morphology [10,11]-is a critical factor of the soil characteristics. Zhai et al [12] found that, for consecutive freeze-thaw cycles, the proportion of micro-pores and mini-pores gradually decreased, while that of meso-pores and macropores increased.…”
Section: Introductionmentioning
confidence: 99%
“…Larew et al [25] proposed a critical cyclic stress ratio, where the soft clay would not be damaged unless the cyclic stress exceeds the critical stress ratio value. Hui et al [6] worked on the redistribution of water and salt in soil under cyclical freeze-thaw. Zhang et al [26] investigated the variation of the microscopic pore structures of silty clay samples before and after freezing-thawing under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%